2011
DOI: 10.1590/s0101-60832011000200007
|View full text |Cite
|
Sign up to set email alerts
|

Influência da resposta individual ao estresse e das comorbidades psiquiátricas na síndrome do intestino irritável

Abstract: ResumoContexto: A síndrome do intestino irritável (SII) é um distúrbio clínico comum, porém ainda pouco compreendida, uma vez que o desenvolvimento dos seus sintomas está fortemente relacionado ao estresse, ansiedade e depressão. Objetivos: Revisar a literatura a fim de verificar se, de fato, existe influência do estresse e das comorbidades psiquiátricas no desenvolvimento, diagnóstico e tratamento para os portadores da SII. Métodos: A revisão foi realizada por meio de pesquisa na base de dados MedLine e Lilac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 34 publications
0
1
0
6
Order By: Relevance
“…In respect to eating disorders, Carvalho et al 9 underlined the relationship between perfectionism and body checking behaviors in males and Sherry and Hall 10 observed that perfectionism increased the risk of binge eating by generating conditions in daily lives that are conducive to binge episodes. Another study 11 showed that personality characteristics, such as a self-demand trait (a construct related to perfectionism, as perfectionists demand perfection of themselves, and self-imposed standards in salient domains that are personally demanding) interfere with intestinal functioning, being associated with irritable bowel syndrome. In fact, recent literature findings support that perfectionism and secondary appraisal are implicated in the stress response, by their association with cortisol increase and HPA axis activation 12. Therefore, perfectionism has a role in the individual response to psychosocial stress and might be a transdiagnostic personality trait implicated in the vulnerability to many psychiatric disorders 13 .…”
Section: Introductionmentioning
confidence: 99%
“…In respect to eating disorders, Carvalho et al 9 underlined the relationship between perfectionism and body checking behaviors in males and Sherry and Hall 10 observed that perfectionism increased the risk of binge eating by generating conditions in daily lives that are conducive to binge episodes. Another study 11 showed that personality characteristics, such as a self-demand trait (a construct related to perfectionism, as perfectionists demand perfection of themselves, and self-imposed standards in salient domains that are personally demanding) interfere with intestinal functioning, being associated with irritable bowel syndrome. In fact, recent literature findings support that perfectionism and secondary appraisal are implicated in the stress response, by their association with cortisol increase and HPA axis activation 12. Therefore, perfectionism has a role in the individual response to psychosocial stress and might be a transdiagnostic personality trait implicated in the vulnerability to many psychiatric disorders 13 .…”
Section: Introductionmentioning
confidence: 99%
“…A partir dessas análises, foi possível identificar que existe uma maior chance de indivíduos com SII apresentarem ansiedade e depressão quando comparados com indivíduos saudáveis. A prevalência de SII nos indivíduos pode variar de acordo com a região estudada uma vez que as diferenças na dieta, os grupos étnicos, a cultura alimentar, estilo de vida, fatores biológicos, psicológicos, socioculturais e o uso de medicamentos podem influenciar significativamente no aparecimento da SII [18][19][20][21] .…”
Section: Discussionunclassified
“…Apesar de alguns estudos sugerirem que a prevalência de ansiedade e depressão é maior nas mulheres 25 para a nossa análise a prevalência entre os sexos foi indiferente. Pode-se afirmar ainda que as estatísticas são falhas quanto ao número de casos de pacientes com SII já que aproximadamente 30% dos pacientes procuram assistência médica 20 . Alguns estudos epidemiológicos apoiam a informação de que a prevalência de depressão em mulheres é aproximadamente duas vezes maior do que em homens 26,27 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Por outro lado, sobre a relação entre constipação, função intestinal e alterações no comportamento, a literatura respalda a afi rmação que alterações de hábitos intestinais como diarreia e/ou constipação, dor abdominal intermitente e outros sintomas estão fortemente relacionados ao estresse, ansiedade e depressão 26 . Ou seja, os problemas intestinais também podem ser expressões somáticas das difi culdades emocionais e comportamentais que a pessoa experimenta, o que reforça a necessidade de estudos comportamentais vinculados a esse quadro em populações especiais.…”
Section: Tabela 2 Tabela De Frequência Dos Critérios Diagnósticos Nounclassified